Factors Affecting Firm Efficiency Of Manufacturing Companies Listed In Indonesia Stock Exchange - Kiky Agustina; Alda Luppianti; Susy Muchtar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This study aims to analyze the effect of financial ratios on company efficiency. This study was conducted using a data sample of 29 manufacturing companies in the various industrial sub-sectors listed on the Indonesia Stock Exchange (IDX) within a reporting period of 5 years (2016 – 2020). The sampling technique uses purposive sampling and uses panel data regression analysis methods. The independent variables in this study consist of leverage, tangibility, working capital, liquidity, productivity, and profitability, while the dependent variable is firm efficiency. The results show that leverage, tangibility, liquidity, and productivity have a significant negative effect on firm efficiency, while working capital, gross profit, and return on equity have no effect on firm efficiency. This finding is expected to be a reference for manufacturing companies in the various industrial sub-sectors in improving company efficiency.